EXPLORING OF STUDENT CHALLENGES IN USING AI FOR LEARNING AND TRANSLATING ACADEMIC TEXTS - Serli, Serli; Rika, Rika; Intan, Pebilia; Tawarik, Oxtapianus (JOEEL (Journal of English Education and Literature), 2025)
Artificial intelligence (AI) has transformed how students understand and acquire knowledge in their educational activities. This research aims to explore how students confront AI challenges and propose solutions to enhance learning and communication. Utilizing quantitative methods or case studies, the findings highlight an urgent need for technological improvements in student education. Most respondents believe in AI; however, some are skeptical about its accuracy and impact on their critical skills. Ethical concerns and plagiarism related to AI are significant, with language barriers affecting users' understanding of new technologies. Respondents tend to choose positive options, indicating optimism but facing difficulties in language comprehension that need to be addressed. The study concludes that students' understanding and skills in using AI for learning are still low. It is recommended to develop training interventions focused on AI comprehension and technical skills, as well as educational policies that effectively support AI integration.